Diagnostic Efficacy and Clinical Significance of Lymphocyte Subsets, Granzyme B and Perforin in the Peripheral Blood of Patients with Invasive Breast Cancer Following Neoadjuvant Chemotherapy - Liu H; Zheng R; Zhuang Z; Xue L; Chen M; Wu Y; Zeng Y (Cancer Management and Research)
Purpose: Breast cancer, a predominant contributor to cancer-related mortality worldwide, is increasingly managed through the application of neoadjuvant chemotherapy (NAC). Analyzing the dynamic changes in peripheral blood lymphocyte subsets, granzyme B and perforin are crucial for investigating their roles in tumorigenesis, development and treatment; this study aimed to use these analyses to diagnose malignant breast tumor, assess the anti-tumor immunity and predict chemotherapy efficacy in breast cancer patients.Patients and Methods: To address this objective, a total of 582 peripheral blood samples were collected from healthy controls (n=47), benign breast disease patients (n=401) and breast cancer patients (n=134). Lymphocyte subsets, along with granzyme B and perforin expression, were assessed using flow cytometry. Changes before and after NAC were also monitored.Results: Breast cancer patients exhibited reduced proportions and absolute counts of CD3+ and CD8+ T cells, increased NK cell percentage and CD4+/CD8+ ratio, and higher levels of granzyme B and perforin in CD3+, CD8+ T cells and NK cells. Post-NAC, the percentages of CD3+, CD4+, CD8+ T cells and NK cells increased, along with a higher CD4+/CD8+ ratio, while B cell percentages decreased compared to pre-NAC. Furthermore, the effective group showed higher percentages of CD3+, CD8+ T cells and lower percentages of B cells than the ineffective group post-NAC. Incidentally, Granzyme B and perforin expression in CD3+ and CD8+ T cells was elevated following postoperative chemotherapy.Conclusion: These findings indicated that peripheral blood lymphocyte subsets, along with granzyme B and perforin levels, could serve as potential biomarkers for differentiating benign from malignant breast tumors, assessing anti-tumor immunity and predicting chemotherapy efficacy.Keywords: breast cancer, lymphocyte subsets, granzyme B, perforin, diagnostic biomarker, neoadjuvant